2019
DOI: 10.33851/jmis.2019.6.4.165
|View full text |Cite
|
Sign up to set email alerts
|

An Intrusion Detection Model based on a Convolutional Neural Network

Abstract: Machine-learning techniques have been actively employed to information security in recent years. Traditional rule-based security solutions are vulnerable to advanced attacks due to unpredictable behaviors and unknown vulnerabilities. By employing ML techniques, we are able to develop intrusion detection systems (IDS) based on anomaly detection instead of misuse detection. Moreover, threshold issues in anomaly detection can also be resolved through machine-learning. There are very few datasets for network intru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 18 publications
0
66
0
Order By: Relevance
“…In [9], a CNN based IDS was proposed by Jiyeon Kim et al In this paper, the authors employed deep learning techniques and developed a CNN model for the CICIDS2018 dataset, which was a dataset sharing the same feature set with CICIDS2017 but with larger sample counts. The training and test of the models in the study were performed on subdatasets which included a subset of types of network traffic from CICIDS2018.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In [9], a CNN based IDS was proposed by Jiyeon Kim et al In this paper, the authors employed deep learning techniques and developed a CNN model for the CICIDS2018 dataset, which was a dataset sharing the same feature set with CICIDS2017 but with larger sample counts. The training and test of the models in the study were performed on subdatasets which included a subset of types of network traffic from CICIDS2018.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, from [7]- [9], it is observed that CNN, albeit with its merits at generalize complex patterns of features in the dataset, has some potential issues at multi-class classifications. The CNN models proposed in these studies are tested on classification tasks of either one-class or a subset of classes in the dataset.…”
Section: A Convolutional Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…In paper [14] the deep learning algorithms capabilities in the network intrusion detection is explored. It compared varity of deep learning frameworks (e.g., TensorFlow,Keras, PyTorch, Theanoand fast.ai) for network traffic intrusion detecting and network attack types classifying .In [15]CIC-2018 dataset and proposed convolutional neural network (CNN) model is implemented, which converted dataset to images, each one in size 13× 6 due to 78 features for each data without the feature Label which used for image classification.…”
Section: Related Workmentioning
confidence: 99%